The Influence of Education and Traning (Training), Work Discipline and Work Orientation on Increasing Work Productivity for New Employees of Perum BULOG 2023 - Ch Endah Winarti; Shafana Robbiyati; Annathasia Puji Erasashanti; Natali Yustisia (Perbanas Institute, 2023)
This study aims to understand and analyze the effect of education and training (training), work discipline, and work orientation on increasing the work productivity of new employees at Perum BULOG 2023. The population of this study are all new employees at Perum BULOG. The independent variables in this study are Education and Training (Training), Work Discipline, and Work Orientation, while the dependent variable in this study is the Work Productivity of New Employees. The research method used is a quantitative research method and is descriptive in nature. The sample method used is a saturated sample with a total of 107 new employees as respondents. Sources of data were obtained from the results of questionnaires and the analysis techniques used, especially multiple linear regression analysis with the help of the SPSS version 20 statistical program. The results showed that: (i) Education and Training (Training) has a positive and significant effect on the Work Productivity of New Perum BULOG Employees; (ii) Work Discipline has a positive and significant effect on the Work Productivity of New Employees of Perum BULOG; (iii) Work Orientation has no effect on the Work Productivity of New Employees of Perum BULOG. .